Double-loaded liposomes encapsulating Quercetin and Quercetin beta-cyclodextrin complexes: Preparation, characterization and evaluation - Shaji, Jessy; Iyer, Sneha (Asian Journal of Pharmaceutics (AJP), 2014)
Beta-cyclodextrin (CD) inclusion complexes of Quercetin were formed and characterized by Differential scanning calorimetry (DSC) and Fourier transform infra-red spectroscopy (FTIR) spectroscopy. Plain Quercetin liposomes using phosphatidylcholine and cholesterol were prepared and optimized. Factors such as ratio of lipids employed, drug:lipid ratio, etc. were fine tuned and optimized to achieve maximum entrapment of the Quercetin into the bilayer. Entrapment was further enhanced by double loading the liposomes. These were prepared by incorporating Quercetin as a plain drug as well as the inclusion complexes within the lipid bilayer and the aqueous compartment, respectively, of the liposomes using the thin film hydration technique. The highest entrapment was achieved with a lipid ratio of 9:1, and the amount of plain drug entering the bilayer was 1/10th the amount of lipid employed. Double loading increased this value to one part of drug per five parts of lipid when Quercetin–beta-CD (1:1 mol/mol) was entrapped. The release of Quercetin from liposomes was highest when the drug was entrapped in the form of a complex with beta cylodextrin. The high entrapment ability of Quercetin in the form of plain drug as well as beta cylodextrin–Quercetin complexes in comparison with plain drug is an indubitable advantage of this approach.